Enhanced Passive Stormwater Infiltration Improves Urban Melia Azedarach Functioning in Dry Season - Gleeson, Xanthia; Johnson, Tim; Lee, Gobert; Zhou, Yifei; Guan, Huade (Frontiers in Climate, 2022)
Urban water management projects involving stormwater harvesting, detention, and infiltration are being increasingly combined with urban greening to support adaptation and resilience to the changing climate. A novel stormwater harvesting device, the TREENET Inlet, intercepts stormwater runoff from roads and soaks it into the soil through a leaky well to provide passive irrigation directly into street tree root zones. This study investigated the effects of stormwater harvesting through these inlet systems on the growth, water-use, leaf-level gas exchange and productivity of white cedar (Melia azedarach) street trees in a semi-arid climate in South Australia. The results indicate that mature trees with TREENET Inlets and leaky wells transpired 17% more water per unit of canopy area per day, on average for about a year, and 21% more during the dry season. White cedar saplings with stormwater harvesting grew 65% more in height and 60% more in diameter at breast height over a 3-year period than saplings without stormwater harvesting. This is consistent with observed 106% greater stomatal conductance and up to 169% greater photosynthesis rate in the dry season for saplings supported by harvested stormwater. This study shows that stormwater harvesting and infiltration by TREENET Inlets provides significant benefit to white cedar trees growing in a suburban street.